Feed preference and growth response of juvenile Litopenaeus vannamei to supplementation of marine chemoattractants in a fishmeal‐challenged diet. Issue 6 (9th September 2019) - Nunes, Alberto J. P.; Sabry‐Neto, Hassan; Oliveira‐Neto, Severino; Burri, Lena
Abstract: This study compared the feed preference and growth response of Litopenaeus vannamei to chemoattractants. A diet with 3% fishmeal was supplemented with either 3% salmon meal (POS), 3% soy protein concentrate (NEG), 3% krill meal (KRM), 3% squid meal (SQM), 3% shrimp head meal (SHM), 3% shrimp meal (SM), 3% squid liver meal (SLM), or 5% liquid sardine hydrolysate (SAH). Shrimp with a body weight (BW) of 0.99 ± 0.08 g were stocked at 100 animals/m 2 in 56 tanks of 1 m 3 and fed 10 times daily for 74 days. Feed preference was evaluated by feeding shrimp of 10.87 ± 1.82 g in excess twice a day for 10 days in two separate feeding trays allocated in 50 tanks of 0.5 m 3 . Survival reached 93.3 ± 5.80% and was unaffected by supplementation. Final BW was the highest for shrimp fed the KRM‐supplemented diet (11.97 ± 0.93 g), followed by POS (11.11 ± 0.77 g) and SQM (11.01 ± 1.17 g). Diets SHM, SM, SLM, and NEG showed a lower shrimp BW than POS, but were not statistically different among them. Shrimp fed the SAH diet achieved the lowest BW (10.06 ± 1.02 g). The highest gained yield was obtained with diets KRM and POS. No statistical difference was observed in shrimp yield among other diets. The lowest feed conversion ratio (FCR) was achieved with shrimp fed KRM (1.31 ± 0.05) when compared to diets SHM (1.47 ± 0.05), SAH (1.47 ± 0.07), and SLM (1.45 ± 0.17). Two‐by‐two comparisons indicated that shrimp preferred SHM and KRM, except when these were compared to SQM and SLM. No difference in feed preference was found between diets with SQM and SLM. SAH was the least preferred raw material in all comparisons. Results indicated that KRM acts as a powerful feeding effector and growth enhancer in fishmeal‐challenged diets for whiteleg shrimp. A dietary supplementation with 3% KRM is more effective than the same dose of any other chemoattractant evaluated.